The use of statistical methodology to determine the accuracy of grading within a diabetic retinopathy screening programme - Oke, JL; Stratton, IM; Aldington, SJ; Stevens, RJ; Scanlon, PH (Wiley, 2015)
Aims We aimed to use longitudinal data from an established screening programme with good quality assurance and quality control procedures and a stable well-trained workforce to determine the accuracy of grading in diabetic retinopathy screening.